IMPLEMENTASI SISTEM INFORMASI REKAPITULASI MANAJEMEN JADWAL KUNJUNGAN (SIREMAJAKU) PRIMAKARA) - Putu Indra Ari Purnama (Journal of Applied Management and Accounting Science, 2019)
In college, a person will study a more specific discipline such as psychology, law, economics, literature, engineering, medicine, and so forth. People who are studying in college are called students (Setiawan). By studying in tertiary institutions, students can gain additional knowledge and insights that can be used in life and to prepare for their future. In addition, by studying in tertiary institutions, students can get a degree, namely a bachelor's degree. Until now, it continues to grow and emerge rapidly with Private Universities with their respective fields of knowledge and excellence in competing to show their charm to attract prospective new students who will study at the College. The tighter competition between private universities, the greater the challenges faced by these private universities to develop their tertiary institutions. One way that can be done by Higher Education the private sector so that they can develop themselves well is by increasing the number of students and maintaining good relations with schools from prospective students.